ҚАЗІРГІ ҚЫТАЙ ТІЛІНДЕГІ КӨП КОМПОНЕНТТІ АНЫҚТАУЫШ - Абдурақын, Н. (Journal of Oriental Studies, 2016)
В статье рассматривается роль и путь образования многокомпонентного сложного в грамматике современ- ного китайского языка. The article considers the role and ways of formation of adjectives consisting o several parts in Moderns Chinese grammer.